Real-World Training for Real-World Benefits: Exploring the Impact of Practice-Based Service Evaluation Training - Price, Matthew James; Latchford, Gary; Hughes, Jan (International Journal of Practice-based Learning in Health and Social Care, 2019)
Service evaluation is a major part of delivering effective healthcare. It is important that the future workforce of clinical psychologists is equipped with the skills required to complete evaluations of the services that they deliver. This article investigated the extent to which practice-based Service Evaluation Projects (SEPs) completed by trainee clinical psychologists at the University of Leeds had an impact on the real-world services that commissioned them. Descriptive analysis was used to summarise the characteristics of SEPs completed over the past thirteen years and to explore feedback from semi-structured interviews held with a sample of commissioners. Thematic analysis was used to identify key themes relating to the impact of SEPs. 230 SEPs have been completed in the past thirteen years. Interviews with 15 commissioners concerning 38 individual SEPs found that the majority had a positive impact (n = 33), most of which were able to bring about a change independently of other initiatives within the service (n = 20). Almost all would have been impossible without the opportunity for clinicians to commission SEPs via the university. Three key themes emerged in terms of impact: improving processes; improving knowledge; and improving resources. Practice-based service evaluations completed by trainee clinical psychologists can lead to a positive impact on real-world services. This suggests that providing training experiences ‘in the field’ is a helpful pedagogical strategy, adding value to services as well as trainee health professionals.